An intersectional perspective on education in Türkiye: Gender, social class, and school type - Tombak Ilhan, Busra (SAGE PUBLICATIONS LTD, 2026)
Mostly focused on gender and race, intersectional research has reminded many scholars that discrimination and inequality in real life are knitted together with multi-layered, connecting strings pertaining to different categories of inequality. In this study, an intersectional lens is used to understand the experiences of female high school students in T & uuml;rkiye. The study broadens the scope of intersectionality through an empirical study where gender, and socio-economic status are analysed in different school types. The data comprised interviews with teachers, female students and their families from three different types of schools and school observations in an urban metropolitan city, Istanbul. The educational experiences of female students from different school types, and socio-economic status and are analysed through the lens of complexity theory. The themes were interpreted with references to the institutional habitus of intersectional inequalities, offering institutional habitus as a new category for intersectionality. The study is relevant to Turkish and wider European contexts.
Keywords: Gender; intersectionality; school type; institutional habitus; socio-economic status; CLASS BOYS; RACE; INEQUALITY; WOMEN; INTERLOCKING; TRANSITION; ETHNICITY; TEACHERS; CRITIQUE; Education & Educational Research